TINJAUAN HUKUM PERLINDUNGAN LINGKUNGAN TERKAIT KEMISKINAN DAN KEAMANAN MANUSIA (HUMAN SECURITY) - Fristikawati, Yanti (Jurnal Paradigma Hukum Pembangunan, 2023)
Humans must be protected from various threats both in times of war or armed conflict, as well as in times of peace. Human protection in times of peace is called Human Security where every individual must not feel threatened and is free to get what he needs, especially his basic needs, which is also called freedom from fear and freedom from want. However, in this part of the world, there is still poverty that threatens their lives, where they cannot fulfill their basic needs, including access to health, poor nutrition for children and good education. One of the causes of poverty is the decline in the quality of the environment, especially for those who rely on nature for their daily lives such as fishermen and farmers, where if the environment is damaged, the catch will decrease and the yield will also decrease. The problem that will be discussed in this paper is how to regulate environmental protection, especially those related to fishermen and farmers to reduce poverty. The research method used is normatif juridical, namely literature review from books, journals, and regulations in Indonesia. One way to overcome poverty is to maintain or protect the environment so that it is not polluted or does not decrease in quality. Arrangements regarding environmental protection and also regarding the protection of fishermen and farmers are needed as an effort to overcome poverty. Regulations in Indonesia are sufficient to protect the environment, apart from that internationally, Sustainable development goals or SDG's have also been proclaimed where the first point of SDG's is "No Poverty", or eliminating poverty. It is expected that good implementation of existing rules is needed so that the environment remains protected and poverty can be overcome.